Biocontrol of Orchid-pathogenic Mold, Phytophthora palmivora, by Antifungal Proteins from Pseudomonas aeruginosa RS1. Issue 2 (3rd April 2018) - Sowanpreecha, Rapeewan; Rerngsamran, Panan
Abstract: Black rot disease in orchids is caused by the water mold Phytophthora palmivora . To gain better biocontrol performance, several factors affecting growth and antifungal substance production by Pseudomonas aeruginosa RS1 were verified. These factors include type and pH of media, temperature, and time for antifungal production. The results showed that the best conditions for P. aeruginosa RS1 to produce the active compounds was cultivating the bacteria in Luria-Bertani medium at pH 7.0 for 21 h at 37 °C. The culture filtrate was subjected to stepwise ammonium sulfate precipitation. The precipitated proteins from the 40% to 80% fraction showed antifungal activity and were further purified by column chromatography. The eluted proteins from fractions 9–10 and 33–34 had the highest antifungal activity at about 75% and 82% inhibition, respectively. SDS-PAGE revealed that the 9–10 fraction contained mixed proteins with molecular weights of 54 kDa, 32 kDa, and 20 kDa, while the 33–34 fraction contained mixed proteins with molecular weights of 40 kDa, 32 kDa, and 29 kDa. Each band of the proteins was analyzed by LC/MS to identify the protein. The result from Spectrum Modeler indicated that these proteins were closed similarly to three groups of the following proteins; catalase, chitin binding protein, and protease. Morphological study under scanning electron microscopy demonstrated that the partially purified proteins from P. aeruginosa RS1 caused abnormal growth and hypha elongation in P. palmivora . The bacteria and/or these proteins may be useful for controlling black rot disease caused by P. palmivora in orchid orchards.